Effect of Food Insecurity on Nutritional Status of Reproductive Age Women of Squatter Settlement of Pokhara Metropolitan, Kaski, Nepal - Paudel, Saru; Bhandari, Tulsi Ram; Paudel, Sanjita; Paudel, Nabaraj (Journal of Karnali Academy of Health Sciences, 2023)
Background: Food insecurity is the situation that exists when all people, at all times, didn’t have secure access to enough amounts of safe and nutritious food that meets their dietary needs for an active and healthy life. However, the nutritional status of women can be determined by family care and household food security as they are keepers of family health. Methods: A cross-sectional study was conducted in the Pokhara Metropolitan squatter settlement. A multistage sampling procedure was used to get the required sample size i.e., 426. Reproductive age group women (15-49 years) were selected because of their central role in food preparation and distribution. Household Food Insecurity Access Scale was used to collect information based on a 30-day recall period. Body mass index (BMI) was calculated based on height and weight measurement. Results: Nearly two-thirds (65%) of household food insecurity was found in the squatter settlement of Pokhara Metropolitan. While assessing the nutritional status of reproductive-age women it was found that 38.1% were overweight and 13.6% were underweight women. Factors such as age, number of dependent family members, educational status, occupational status, age at marriage, age at first pregnancy, parity, number of children, and household food insecurity were associated with respondents’ BMI at the 95% confidence level. Conclusion: Nearly two-thirds of the respondents had household food insecurity and most of them in those households were likely to be overweight or underweight. The study highlights a need for nutrition and food security programs.